2020
DOI: 10.1007/s40520-020-01727-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of nutritional status in elderly patients hospitalized for COVID-19: a monocentric study

Abstract: Background Symptomatic severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection incidence is higher in the elderly patients. Pre-existing geriatric conditions such as comorbidity and frailty seem related to worse hospital outcomes. Aims To assess the role of nutritional status as an independent prognostic factor for in-hospital death in elderly patients. Methods Consecutive elderly patients (age > 65 years) hospitalized for novel coronavirus disease (COVID-19) were enrolled. Demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 46 publications
1
47
0
4
Order By: Relevance
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
“…Dabei erhöht das Vorliegen einer Mangelernährung eindeutig das Risiko für einen schweren bzw. tödlichen Verlauf einer COVID-19-Erkrankung [ 54 ]. Dass eine Mangelernährung auch das Risiko für das Auftreten einer SARS-CoV-2-Infektion erhöht, wird vermutet, ist aber bisher nicht bewiesen.…”
Section: Die Rolle Der Ernährungunclassified
“…Currently, some studies are reporting on the nutritional status of older patients affected by COVID-19, as it may serve as a prognostic tool for their recovery. In that line, Racinella et al examined the nutritional status of over 100 men and women (≥65 years) hospitalized for COVID-19 and reported that their Geriatric Nutrition Risk Index was a significant predictor for survival, even after some confounders were taken into account [ 25 ]. Importantly, in one of the earlier studies conducted in Wuhan elderly patients ( n = 182), 52.7% were diagnosed with malnutrition (via Mini Nutritional Assessment) and also characterized as having diabetes, a smaller calf circumference and lower serum albumin, placing them at disadvantageous outcomes in infection recovery [ 26 ].…”
Section: Precision Nutrition For Osa and Lgci In Good Times And Inmentioning
confidence: 99%